A Discussion on the Nature of Insurance Premium Incentives Applied in Turkey: Public Expenditure or Premium Expenditure? - Mehmet Bulut (Maliye Çalışmaları Dergisi)
Insurance premium incentives are an essential active employment policy in the fight against unemployment. They are also relevant to achievingmany financial and social policy objectives. With insurance premium incentives, the premium burden on the employer and/or the insured is reduced, and the goal is to achieve results, such as protecting existing employment, reducing unemployment, preventing unregistered employment, introducing policies for certain sectors and regions, and providing employment for specific groups of people. Therefore, achieving these goals can only be possible if the incentive system is applicable, concise, and accurate in scope. Turkey currently has 17 different insurance premium incentives implemented, most of which are public expenditures and they carry challenges, such as lack of inter-institutional coordination, technical and legal challenges, and complexity in practice. In this study, explanations were given regarding the determination of the nature of insurance premium incentives applied in Turkey, as well as the observed challenges. Furthermore, the concept of premium expenditure was employed for the first time in an academic study in Turkey, and a comparison was made with the concept of public expenditures, and thus, making this study significant in terms of finance literature.